MANAJEMEN KONFLIK DI MADRASAH/SEKOLAH - Muhammad Afif Nurochim; Dr. Hj. Mardiyah, M.Ag; Rachmadonna Retno Anggraeny (FKIP, Universitas Palangka Raya, 2023)
In any organization, there will be conflict. The principle is that the highest ranking official in the school, if appropriate to determine the circumstances that led to the dispute. The different ways concepts are interpreted, the conflicting goals and objectives that must be met, and the misalignment between the two caused by a lack of resources all work to the strength or shape advantage of one party at the expense of the other. Inadequate organizational and communication resources can lead to ugly conflicts, differences in traits, values, and perceptions, task interdependence, pay systems, and limited organizational resources. Using negotiation as a conflict resolution tactic Here, two processes are suggested. Opposing groups get together to discuss their disagreements and try to reach an understanding by making offers, counter-offers, and compromises. Third party mediators, or invite third parties to take a neutral stance to help the disputing parties reach a settlement; third party negotiators, or invite third parties who are specialists in tenders and negotiations. the dispute, and authorized agents or third parties. resolve disputes between conflicting parties